Práticas pedagógicas construídas na Escola Rural Multisseriada: o movimento de afirmação e transgressão do modelo seriado de ensino na Amazônia Amapaense - CUNHA, Suany Rodrigues da (2017)
The present study aims to investigate the pedagogical practices built in the rural multi-serialized school, aiming to identify aspects that point to affirmation and transgression of the serial teaching model in Amazônia Amapaense. It is justified to seek to understand the vision we have about the multiseries and its implication for the construction of pedagogical practices, paying attention to the specificities of work through the regulation of time, organization of the learning space and systematization of knowledge. The study is based on the following: What aspects emerge in the pedagogical practices built in the multi-serialized rural school that point to the affirmation and transgression of the serial teaching model in Amazônia Amapaense? For this study the qualitative research was indicated, with the adoption of the dialectical method and the type of case study, having as instruments the observation in locus, semi-structured interview and photographic records. The results of the research indicate that the conceptions of the teachers investigated on the multiseries imply in the construction of their pedagogical practices, focusing on the discrepancy of the positions on the profile of the classes, perception of the heterogeneity of the subjects, conditioners of the regulation of the time, organization of the learning space And systematization of knowledge. These references make it possible to identify in the didactic-methodological strategies assumed by the pedagogical practices of the teachers, aspects that contribute so much to the affirmation of the pillars as to the transgression of the serial model of teaching revealing contradictions inherent in the construction of the pedagogical practice.